ANALISIS TRANSAKSI VALUTA ASING (AL-SHARF): Tinjauan Hukum Ekonomi Islam di Indonesia - A. Ika Fahrika; H. Muhtar Lutfi; Nasrullah Bin Sapa (IAIN BONE, 2022)
Abstract. Analysis of Foreign Exchange Transactions (Al-Sharf): An Overview of Islamic Economic Law in Indonesia. The purpose of this research is to find out how the legal view of Indonesian Islamic Economics regarding foreign exchange (Al-Sharf), which is one of the transaction tools to meet basic human needs around the world today. The buying and selling of currencies is permitted as long as the transactions made are paid in cash and the local currency exchange rates are converted to the exchange rates of the currencies being exchanged. The study conducted by the author with an approach to norms and sources of Islamic law that specifically applies in Indonesia. In this study, the author will conduct a literature review of books and documents that discuss foreign exchange trading, as well as examine and analyze them from the perspective of Islamic economic law. Abstrak Tujuan dari diadakannya penelitian ini adalah untuk mengetahui bagaimana pandangan hukum Ekonomi Islam Indonesia mengenai valuta asing (Al-Sharf), yang merupakan salah satu alat transaski yang untuk memenuhi kebutuhan dasar manusia di seluruh dunia saat ini. Pembelian dan penjualan mata uang diizinkan selama transaksi yang dilakukan dibayar secara tunai dan nilai tukar mata uang lokal dikonversi ke nilai tukar mata uang yang ditukarkan. Kajian yang dilakukan oleh penulis dengan pendekatan norma dan sumber hukum Islam yang khusus berlaku di Indonesia. Dalam penelitian ini, penulis akan melakukan kajian literatur terhadap buku-buku dan dokumen-dokumen yang membahas tentang perdagangan valuta asing, serta mengkaji dan menganalisisnya dari perspektif hukum ekonomi Islam.